Hyperbilirubinemia in atazanavir-treated human immunodeficiency virus-infected patients: the impact of the UGT1A1*28 allele - Naidoo A; Naidoo K; Ramsuran V; Reddy M; Padayatchi N (Dove Medical Press, 2017)
Anushka Naidoo,1 Kogieleum Naidoo,1,2 Veron Ramsuran,3 Millidhashni Reddy,1 Nesri Padayatchi1,2 1Centre for the AIDS Programme of Research in South Africa, 2MRC-CAPRISA HIV-TB Pathogenesis and Treatment Research Unit, Doris Duke Medical Research Institute, 3School of Laboratory Medicine and Medical Sciences, University of KwaZulu-Natal, Durban, South Africa Panagopoulos et al1 reviewed the effects of the UGT1A1*28 polymorphism on Reyataz® (atazanavir)-related hyperbilirubinemia in human immunodeficiency virus (HIV)-infected patients that may result in increased severity and drug discontinuation in some patients. The effects of the UGT1A1 polymorphisms on the pharmacokinetics of other antiretroviral drugs such as Isentress® (raltegravir) and Edurant® (rilpivirine) are also discussed. We respond here on the relevance of the study findings in the South African context.  View the original paper by Panagopoulos and colleagues.